Exon junction complex-associated multi-adapter RNPS1 nucleates splicing regulatory complexes to maintain transcriptome surveillance - Schlautmann, Lena P.; Lackmann, Jan-Wilm; Altmüller, Janine; Dieterich, Christoph; Böhm, Volker; Gehring, Niels H. (Nucleic acids research, 2022)
The exon junction complex (EJC) is an RNA-binding multi-protein complex with critical functions in post-transcriptional gene regulation. It is deposited on the mRNA during splicing and regulates diverse processes including pre-mRNA splicing and nonsense-mediated mRNA decay (NMD) via various interacting proteins. The peripheral EJC-binding protein RNPS1 was reported to serve two insufficiently characterized functions: suppressing mis-splicing of cryptic splice sites and activating NMD in the cytoplasm. The analysis of transcriptome-wide effects of EJC and RNPS1 knockdowns in different human cell lines supports the conclusion that RNPS1 can moderately influence NMD activity, but is not a globally essential NMD factor. However, numerous aberrant splicing events strongly suggest that the main function of RNPS1 is splicing regulation. Rescue analyses revealed that the RRM and C-terminal domain of RNPS1 both contribute partially to regulate RNPS1-dependent splicing events. We defined the RNPS1 core interactome using complementary immunoprecipitations and proximity labeling, which identified interactions with splicing-regulatory factors that are dependent on the C-terminus or the RRM domain of RNPS1. Thus, RNPS1 emerges as a multifunctional splicing regulator that promotes correct and efficient splicing of different vulnerable splicing events via the formation of diverse splicing-promoting complexes.
Gesehen am 25.09.2024